Peran Fasilitator Pendamping Terhadap Pengembangan Usaha Nasabah Prasejahtera BTPN Syariah - Sidiq Musyafa; Suhud Munfadil; Elok Ainur Latif (As-Syirkah: Islamic Economic & Financial Journal, 2025)
The Certified Independent Internship and Study Program (MSIB) is part of the Merdeka Belajar Kampus Merdeka (MBKM) policy by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek). PT. Bank BTPN Syariah TBK is one of the partners of the MSIB Batch 3 program. Bank BTPN Syariah provides an intermediary as a facilitator to support customers in achieving their expected goals. The role of the assistant here is to help customers maximize sales. BTPN Syariah customers as ultra-micro actors who receive facilities in the form of assistants so that they can help them develop their businesses. The assistant facilitators provided by Bank BTPN Syariah aim to support the empowerment activities of BTPN Syariah customers, especially women/mothers from productive underprivileged communities or micro entrepreneurs, who have the capacity and skills along with customer skills in running their businesses, so that they can develop further and open wider market access, both offline and online.